2013
DOI: 10.2147/ijnrd.s35632
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate control in dialysis

Abstract: Prevention and correction of hyperphosphatemia is a major goal of chronic kidney disease-mineral and bone disorder (CKD-MBD) management, achievable through avoidance of a positive phosphate balance. To this aim, optimal dialysis removal, careful use of phosphate binders, and dietary phosphate control are needed to optimize the control of phosphate balance in well-nourished patients on a standard three-times-a-week hemodialysis schedule. Using a mixed diffusive-convective hemodialysis tecniques, and increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
11

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 88 publications
3
48
0
11
Order By: Relevance
“…For preplanned comparisons across dosing regimens, the 24-hour urine collections from the last 4 days of each period were examined. For comparisons with baseline, the individual results from all three dosing regimens for the last 4 days (days [19][20][21][22] were averaged and compared with the four baseline days (4-day analysis). To validate that the findings were not influenced by the short baseline period, a sensitivity analysis was conducted, in which the last 2 days of the baseline period were also compared with the last 2 days of the final treatment period (days 21 and 22) for urine excretion of K, Na, Ca, Mg, and P (2-day analysis).…”
Section: Methodsmentioning
confidence: 99%
“…For preplanned comparisons across dosing regimens, the 24-hour urine collections from the last 4 days of each period were examined. For comparisons with baseline, the individual results from all three dosing regimens for the last 4 days (days [19][20][21][22] were averaged and compared with the four baseline days (4-day analysis). To validate that the findings were not influenced by the short baseline period, a sensitivity analysis was conducted, in which the last 2 days of the baseline period were also compared with the last 2 days of the final treatment period (days 21 and 22) for urine excretion of K, Na, Ca, Mg, and P (2-day analysis).…”
Section: Methodsmentioning
confidence: 99%
“…Studies show increased death risk as the result of hyperphosphatemia among patients under hemodialysis. One of the important solutions to achieve this goal is to receive balanced nutrition (18). Hyperkalemia, due to decreased potassium secretion, is also common among patients with CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that PD is associated with more abnormalities in phosphorous and albumin than HD, especially once residual renal function has deteriorated. 21,22 Thus, it is possible that our data suggest that those PD patients who have difficulty controlling phosphorus or maintaining their albumin may be at increased risk of calciphylaxis.…”
Section: Calciphylaxis In Peritoneal Dialysismentioning
confidence: 94%